PSYCHOLOGICAL FEATURES OF PROFESSIONAL MOTIVATION OF STUDENTS OF THE FIELD OF PRACTICAL PSYCHOLOGY DURING MARTIAL LAW - Ломакін, Геннадій; Сапєльнікова, Тетяна (SWorldJournal, 2025)
The paper examines the professional motivation of students majoring in practical psychology during martial law in Ukraine. Professional motivation is one of the key factors that determine a student’s success in the learning process and future professiona